Preference reversal and group strategy-proofness. - Berga, Dolors; Moreno-Jiménez, Bernardo (Elsevier, 2020)
We study the problem of choosing one alternative given agent’s strict preferences. We show that preference reversal (Eliaz, 2004) implies group strategy-proofness. Moreover, they are equivalent for the special cases where only two or three alternatives may be chosen.
https://openpolicyfinder.jisc.ac.uk/id/publication/15557
Keywords: Juegos, Teoría de; Social choice function; Group strategy-proofness; Preference reversal